Evaluación de la inmunoesterilización como alternativa a la esterilización quirúrgica tradicional en diferentes parámetros hormonales en cuyes (cavia porcellus) como modelo experimental en el Ceypsa - Falconi Heredia, Erika Alexandra (2015)
The present investigation was made with the purpose of get a new alternative, avoiding potential complications to with a surgical process, for such reason the objective of this investigation was to determine the effect of immunosterilisation as an alternative to traditional surgical sterilization in different hormonal parameters in cuyes (cavia porcellus) as experimental model on the Ceypsa. It was used 15 cuyes males, for the investigation divided in to 3 treatments: Inmunoesterilizados were applied 4 doses of anti-GnRH, with a dose the 0.3ml by subcutaneously, was analyzed LH, FSH, testosterone and cortisol before and after application of the vaccine. Treatment consisted of surgically sterilized subjecting animals to traditional sterilization technique to measure the level of stress and pain suffered an analysis of LH, FSH, testosterone and cortisol before and after surgical sterilization is also performed. The group of control animals was measure hormone levels of LH, FSH, testosterone and cortisol. A morphometric and histological study of the testes of all animals was performed. Treatment (IE) determined a mean 0.27mUI / ml of LH, 0.9mUI / ml of FSH, 0.75ng / ml Testosterone, 31.18ng / ml cortisol post-testing. Treatment (EQ) determined a mean 0.27mUI / ml of LH, 0.97mUI / ml of FSH, 0.05ng / ml Testosterone, 29.08ng / ml cortisol post-experiment. The control group found half of 0.29mUI / ml of LH, 0.93mUI / ml of FSH, 2.5ng / ml Testosterone, 23.43ng / ml cortisol post-experimentation....